Subordinates’ Perceptions of Managers’ Listening Effectiveness - Levy, Deborah (My University, 2014)
Although listening is a key component of communication and organisational functioning, this field has been somewhat neglected and understudied. This is particularly true in comparison to other interpersonal and communication skills and with regard to listening’s importance to the workplace and organisations. The benefits of listening in the workplace have been assumed rather than tested as little evidence in this regard has been presented in the literature. This study investigates the relationship between subordinate perceptions of managerial listening effectiveness and subordinate satisfaction with these managers. Over four hundred management and executive students with work experience were surveyed with questionnaires in order to determine both their satisfaction with their managers and their perceptions of their managers’ listening effectiveness. Using Rho factor analysis, two factors of association were found to exist between management listening and subordinate satisfaction. The first factor is the manager’s orientation and the second is managers’ engagement. The manager’s orientation consists of a focus on task and accuracy (composed of remembering significant details, giving straightforward responses and remembering significant details of past conversations), and on supportiveness and relationship (composed of taking time to listen, making others feel at ease and not making negative statements when listening). The manager’s engagement exists both during the listening interaction (consisting of making eye contact when listening, expressing ideas or opinions, using positive nonverbal expressions and hearing inconsistencies in fact and logic) and after the listening interaction (which includes responding appropriately, making reference to and taking action). This study associates particular aspects of subordinate satisfaction with specific aspects of managerial listening. From this research, it is evident that subordinate satisfaction is associated with managers who display and engender a balanced and well considered approach to listening.
MBA thesis
Keywords: Listening skills; People management